Energy availability and dietary patterns of adult male and female competitive cyclists with lower than expected bone mineral density - Viner, R. T.; Harris, M.; Berning, J. R.; Meyer, N. L. (International Journal of Sport Nutrition and Exercise Metabolism, 2015)
The purpose of this study was to assess energy availability (EA) and dietary patterns of 10 adult (29-49 years) male (n = 6) and female (n = 4) competitive (USA Cycling Category: Pro, n = 2; 1-4, n = 8) endurance cyclists (5 road, 5 off-road), with lower than expected bone mineral density (BMD; Z score < 0) across a season. Energy intake (EI) and exercise energy expenditure during preseason (PS), competition (C), and off-season (OS) were estimated from 3-day dietary records, completed once per month, across a cycling season. BMD was measured by DXA at 0 months/5 months/10 months. The Three-Factor Eating Questionnaire (TFEQ) was used to assess cognitive dietary restraint. Seventy percent of participants had low EA [(LEA); < 30 kcal·kg fat-free mass (FFM) -1·day-1] during PS, 90% during C, and 80% during OS (range: 3-37 kcal·kg FFM-1·day-1). Ninety percent of cyclists had LEA during = 1 training period, and 70% had LEA across the season. Seventy percent of cyclists were identified as restrained eaters who consciously restrict EI as a means of weight control. Mean daily carbohydrate intake was below sport nutrition recommendations during each training period (PS: 3.9 ± 1.1 g·kg-1·day-1, p < .001; C: 4.3 ± 1.4 g·kg-1·day-1, p = .005; OS: 3.7 ± 1.4 g·kg-1·day-1, p = .01). There were no differences in EA and EI·kg-1 between male and female cyclists and road and off-road cyclists. Low EI, and specifically low carbohydrate intake, appears to be the main contributor to chronic LEA in these cyclists. Adult male and female competitive road and off-road cyclists in the United States may be at risk for long-term LEA. Further studies are needed to explore strategies to prevent and monitor long-term LEA in these athletes.